Informal education in the festivity of the crosses in Huaraz - Olórtegui-Mariño, Rufa (2026)
This study investigates the Festivity of the Crosses of Taita Runtu and Taita Awaq in the village of Paria, Huaraz (Peru), as a space for informal learning. Employing a qualitative ethnographic method, the research utilized participant observation and semi-structured interviews. The findings reveal that the festivity encompasses both content (what is learned) and forms (how it is learned) of informal learning. These learnings are intricately linked to religious devotion, the festive processes, and community participation. They contribute to social integration, the development of communal values, and harmonious coexistence. In conclusion, the study identifies the development of a diverse set of learnings within the framework of informal learning. The contents learned include knowledge, skills, religious devotion, attitudes, and social practices essential for community life. The forms of learning observed encompass participating, doing, asking, helping, accompanying, listening, observing, sharing, and practicing. Both the content and forms of learning, alongside overall observations, highlight that the Festivity of the Crosses, by engaging all participants, significantly strengthens integration ties and the practice of communal values